Detailed analysis of a randomized, multicenter, comparative trial of dienogest versus leuprolide acetate in endometriosis - Strowitzki, Thomas (International journal of gynecology & obstetrics, 2012)
Objective To analyze the secondary efficacy and safety outcomes from a recent trial comparing dienogest (DNG) with leuprolide acetate (LA) in women with endometriosis. Methods A 24-week, open-label, randomized, multicenter study of DNG versus LA in women with endometriosis-related pain was assessed for outcomes such as responder rates (using predefined thresholds of pain relief), changes in single symptoms/signs and sum scores from the Biberoglu and Behrman (B&B) scale, clinical laboratory parameters, and measures of quality of life. Results Dienogest was non-inferior to LA for treatment response using all predefined thresholds of pain relief and provided equivalent improvements in B&B symptoms and signs. No clinically relevant changes in laboratory parameters were observed during DNG treatment, whereas estrogen levels decreased in the LA group. Compared with LA, DNG was associated with pronounced improvements in specific quality-of-life measures. Conclusion The analyses provide supportive evidence that the efficacy of DNG is equivalent to that of LA for treating endometriosis symptoms, with specific quality-of-life benefits and a favorable safety profile.